2012
DOI: 10.1002/chem.201200621
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis, Structural Investigations, Ligand Tuning and Synthetic Evaluation of Silyloxy‐Based Alkyne Metathesis Catalysts

Abstract: Nitride- and alkylidyne complexes of molybdenum endowed with triarylsilanolate ligands are excellent (pre)catalysts for alkyne-metathesis reactions of all sorts, since they combine high activity with an outstanding tolerance toward polar and/or sensitive functional groups. Structural and reactivity data suggest that this promising application profile results from a favorable match between the characteristics of the high-valent molybdenum center and the electronic and steric features of the chosen Ar(3)SiO grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
290
0
43

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(337 citation statements)
references
References 122 publications
4
290
0
43
Order By: Relevance
“…Worth to be reminded at this point is the fact that the kinetic studies have shown a first order dependence of the reaction rate in phenol concentration, which may here be justified, if considering that this protonolysis reaction would be the rate determining step. Among others such as triphenylsiloxy molybdenum carbynes recently studied in depth by Heppekausen et al [32], these aryloxy species are known to be ideal ligands to provide active molybdenum carbyne complexes for alkyne metathesis, as compared with tungsten-based catalysts [33]. Figure 6 is representative of the preceding hypothesis, where the production of a (PhO) 2 Mo transient intermediate is therefore suggested, following the preliminary molybdenacyclopentadiene complex formation.…”
Section: Discussionmentioning
confidence: 84%
“…Worth to be reminded at this point is the fact that the kinetic studies have shown a first order dependence of the reaction rate in phenol concentration, which may here be justified, if considering that this protonolysis reaction would be the rate determining step. Among others such as triphenylsiloxy molybdenum carbynes recently studied in depth by Heppekausen et al [32], these aryloxy species are known to be ideal ligands to provide active molybdenum carbyne complexes for alkyne metathesis, as compared with tungsten-based catalysts [33]. Figure 6 is representative of the preceding hypothesis, where the production of a (PhO) 2 Mo transient intermediate is therefore suggested, following the preliminary molybdenacyclopentadiene complex formation.…”
Section: Discussionmentioning
confidence: 84%
“…Diese Katalysatoren werden durch reversible Adduktbildung mit Phenanthrolin sogar luftstabil und sind somit bequem und sicher handhabbar (Abbildung 5). [114,115] Komplex 16 und seine Analoga sind dem klassischen Katalysator [(tBuO) 3 W CCMe 3 ] an Aktivität weit überle-gen (Abbildung 6). Noch wichtiger ist jedoch ihre exzellente Kompatibilität mit polaren und unpolaren Substituenten, die an die Chemoselektivität vieler edelmetallbasierter Katalysatoren heranreicht.…”
Section: Methodsunclassified
“…[115] Außerdem wurde eine flexible und skalierbare Methode zur Synthese von 16 und der stabilisierten Variante 17 entwickelt, die beide mittlerweile auch kommerziell verfügbar sind. Auch die Zerfallswege dieser Katalysatoren wurden eingehend untersucht, um künftige Studien auf eine rationalere Basis zu stellen.…”
Section: Methodsunclassified
“…So erwies sich etwa Verbindung 42 in kristalliner Form an der Luft als praktisch unbeschränkt (> 2 Jahre) stabil, was das Arbeiten beträcht-lich erleichtert. [68,69,75] Während …”
Section: Angewandte Aufsätzeunclassified
“…Auf dem in Schema 11 gezeigten Weg wurden der Arylrest Ar an der Alkylidineinheit ebenso variiert wie der Gürtel der Silanolatgruppen und der zur Stabilisierung bençtigte N-Donor-Ligand. Die Ergebnisse einer umfangreichen und systematischen Untersuchung lassen sich wie folgt zusammenfassen: [68,69,78] Daneben sind Verbindung 50 sowie die daraus abgeleitete stabile Variante 51 ebenfalls bevorzugte Katalysatoren (Abbildung 3), die vor allem bei sehr lipophilen Substraten zum Einsatz kommen sollten. Die MeO-Gruppen sorgen nämlich dafür, dass die bei der Aufarbeitung der Reaktionsgemische aus den Katalysatoren gebildeten siliciumhaltigen Nebenprodukte ausreichend polar und somit leicht vom gewünsch-ten Produkt abtrennbar sind.…”
Section: Alkinmetatheseunclassified